The ‘Step by Step’ Diabetic Foot Project in Tanzania: a model for improving patient outcomes in less‐developed countries - Abbas, Zulfiqarali G (Int Wound J, 2011)
Foot complications cause substantial morbidity in Tanzania, where 70% of leg amputations occur in diabetic patients. The Step by Step Foot Project was initiated to train healthcare personnel in diabetic foot management, facilitate transfer of knowledge and expertise, and improve patient education. The project comprised a 3‐day basic course with an interim period 1‐year of for screening, followed by an advanced course and evaluation of activities. Fifteen centres from across Tanzania participated during 2004–2006 and 12 during 2004–2007. Of 11 714 patients screened in 2005, 4335 (37%) had high‐risk feet. Of 461 (11%) with ulcers, 45 (9·8%) underwent major amputation. Of 3860 patients screened during 2006–2007, there was a significant increase in the proportion with ulcers and amputations compared with 2005 (P < 0·001), likely a result of enhanced case finding. During 2005–2008, there was a fall in the incidence of foot ulcers in patient referrals to the main tertiary care centre in Dar es Salaam and a parallel fall in amputation among these referrals. In conclusion, the Step by Step Foot Project in Tanzania improved foot ulcer management for persons with diabetes and resulted in permanent, operational foot clinics across the country. This programme is an effective model for improving outcomes in other less‐developed countries.